THE STRATEGY OG INDONESIAN GOVERNMENT TO RECOVER TOURISM IN BALI AFTER BALI BOMBING (2007-2012) - Rizky Ayu Kurniasari (HI 16 UMY 104, 2016)
*104 Tourism is one of the industries that has relevance to a wide range of economic activities and also tourism is one of the important contribution in increasing national income. Indonesia has potential to develop because Indonesia is an archipelago country with thousand island and million cultural diversity. Talking about tourism in Indonesia, Bali is one of the favorite tourism destinations of foreign tourists all over the world. But unfortunately, tourism in Indonesia had deteriorated quite dramatically. The existence of the Bali bombings in 2002 and 2005 resulted in the number of foreign tourists who did not want to come to Indonesia because of fear. Bali bombings that killed hundreds of foreign tourists who make the international community is reluctant to visit for a vacation in Bali. It becomes interesting question to know what are the stategies of Indonesian government to recover tourism in Bali. Because this thesis will analyze the strategy of Indonesian government in developing tourism sector after Bali Bombing by improving the facility services and also promoting in international level, also the implementation of Visit Indonesia Year 2008 as a main tool and the achievement also continuation this program in 5 years. In this thesis the writer uses library research method to collect the data from literatures, newspapers, journals, internet, also observation in Bali and visiting the place where the bombing was happened and do some simple interviews with people who has tourism industries. As a result Visit Indonesia Year 2008 to become the flagship program of the current government with the success of approaching the amount of traffic that is targeted and collect income reach US $ 7.1 billion. It is used as a milestone in the rise of Indonesia while optimizing tourism promotion inside and outside with the continuation of this program. Visit Indonesia Year (VIY) 2008 is the successful program of brand campaign as the main tool of diplomacy to convince foreign tourists and the lifting of travel warnings from various countries as well as restore Indonesian tourism, especially in Bali after two bombing tragedies at that time. Keywords : Tourism, Strategy, Recover, Bali Bombing